Efficient Data Processing and Consensus Algorithms for Resource-Constrained Wireless Sensor Networks in Environmental Monitoring: Survey - Sherzod Turaev, Mohammed A. H. Ali, Abdullah Said AL-Aamri, Yousuf Al Husaini, Mohammed Abdulla Salim Al Husaini, Rawad Abdulghafor (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research paper focuses on the applications and challenges of wireless sensor networks (WSNs). WSNs consist of small, low-cost sensors that can collect and process data in various fields such as military, environmental monitoring, health, home appliances, and other commercial applications. The paper discusses the benefits of structured deployments over ad hoc deployments and highlights the resource constraints of sensor nodes, including limited energy, communication range, and processing capabilities. It emphasizes the importance of clustering sensor nodes and utilizing sophisticated routing protocols for data transfer to fusion centers. The research also explores consensus algorithms for achieving global statistics in WSNs while sharing data with close neighbors. Various applications of WSNs are discussed, including military operations, environmental monitoring, health monitoring, home automation, and commercial uses. The paper presents a literature review on topics such as distributed consensus algorithms, multi-agent systems, and coordination control in WSNs. It covers topics like average consensus, event-triggered consensus control, nonlinear multi-agent networks, and consensus in stochastic networks. The research highlights the challenges and potential solutions for achieving consensus in WSNs, considering factors such as switching topology, communication delays, and uncertain nonlinear dynamics. Overall, this paper provides insights into the applications, challenges, and consensus algorithms in wireless sensor networks.